PERAN EMOSI POSITIF MEMEDIASI PENGARUH FASHION INVOLVEMENT DAN HEDONIC CONSUMPTION TENDENCY TERHADAP IMPULSE BUYING - Kinasih, Ida Ayu Diksita; Jatra, I Made (E-Jurnal Manajemen, 2018)
The purpose of this study was to examine the effect of fashion involvement and hedonic consumption tendency on positive emotions, the influence of fashion involvement, hedonic consumption tendency and positive emotion on impulse buying, and the role of positive emotions mediate the influence of fashion involvement and hedonic consumption tendency toward impulse buying on fashion products Discovery Shopping Mall Kuta. The method used to determine the sample is non-probability in the form of purposive sampling with sample size of 105 respondents. Data collection was done by distributing questionnaires directly to customers of fashion products Discovery Shopping Mall Kuta. The analysis technique used is path analysis and sobel test. There is a positive and significant relationship between fashion involvement and hedonic consumption tendency toward positive emotion, positive and significant relationship between fashion involvement, hedonic consumption tendency and positive emotion toward impulse buying. Positive emotions can act as significant mediation variables between the influence of fashion involvement and hedonic consumption tendency toward impulse buying.